Prevalence of vitamin D deficiency in exclusively breastfed infants - Velusamy, Prabu; Devarajulu, Kavitha (International Journal of Contemporary Pediatrics, 2019)
Background: Vitamin D deficiency in exclusively breast fed infants was increasing in young infants. Many studies were done previously but still the data on vitamin D status of healthy term infants are scanty. Hence the present study was done to determine the prevalence of subclinical vitamin D deficiency among exclusively breast fed babies by estimating the serum levels of relevant parameters. Methods: The present descriptive study included 40 babies that are exclusively breast fed healthy term babies with birth weight >2.5kg. After collection of complete demographic and antenatal data, serum was collected from all the babies to estimate serum levels of vitamin D (25OH-D3) and calcium, phosphate, and alkaline phosphatase. Results: Out of 40 babies, vitamin D deficiency was found in 33 (83%) babies. Of them, hypocalcaemia was seen in 13 (39.3%) infants. Raised ALP was noticed in all babies with a mean value of 464.97 IU/L. Phosphorus levels were normal in all babies with a mean value of 6.12 mg/ml. Serum 25 OH vitamin D3 levels were low (mean-10.02 ng/ml) and mean calcium was 8.81 mg/dl. Conclusions: Prevalence of vitamin D deficiency was found to be high in exclusively breastfed babies with hypocalcemia in 39% of babies and associated seizure in one baby in this study.